Ovarian cancer in Western Australia (1982-98): incidence, mortality and survival - Crystal L. Laurvick; James B. Semmens; C. D'Arcy J. Holman; Yee C. Leung (Elsevier, 2003)
Abstract Objectives: To investigate the trends in incidence and mortality and estimate survival for women diagnosed with ovarian cancer in Western Australia. Case selection and methods: There were 1,336 women diagnosed with ovarian cancer in 1982-98. Age‐standardised rates were calculated by the direct method. Age‐period and age‐cohort models were analysed by Poisson regression. The Kaplan‐Meier method was used to estimate survival and Cox proportional hazards regression evaluated the relative risk of dying. Results: Trends in age‐adjusted incidence and mortality rates showed little changed over the three time periods of diagnosis. A significant birth cohort effect showed a peak in the risk in the 1924 (mid‐year) cohort followed by a general decrease in both incidence and mortality risk. Survival at five years was 34% (95% CI 31.3-36.5) overall, but was only 27% (95% CI 17.4-36.7) among women with stage III and IV disease. Aboriginal women showed a risk of dying twice that of non‐Aboriginal women. Conclusions: The birth cohort analysis of ovarian cancer proved better at explaining disease trends than was time period of diagnosis. Survival continues to be poor, but Aboriginal women and those with serous and unspecified adenocarcinoma tumours fair much worse. Implications: As the leading cause of death from a gynaecological malignancy, ovarian cancer is of public health importance. Historical trends in birth rates and the use of oral contraceptives help to explain at least some of the observed birth cohort trends in this study. In the long term, an effective diagnostic technique needs to be developed or this disease will continue to be diagnosed at an advanced stage when treatment options for cure are limited.